2010
DOI: 10.1120/jacmp.v11i3.3227
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of various optimization techniques for high dose rate brachytherapy of interstitial cervix implants

Abstract: HDR brachytherapy treatment planning often involves optimization methods to calculate the dwell times and dwell positions of the radioactive source along specified afterloading catheters. The purpose of this study is to compare the dose distribution obtained with geometric optimization (GO) and volume optimization (VO) combined with isodose reshaping. This is a retrospective study of 10 cervix HDR interstitial brachytherapy implants planned using geometric optimization and treated with a dose of 6 Gy per fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Sharma et al used Paris technique for dose prescription and found that DHI, DNR, and COIN were 0.61, 0.31, and 0.79, respectively [22]. Swetha et al reported DHI, DNR, and COIN as 0.57, 0.43, and 0.73, respectively, in their study using inverse planning technique [23]. In the present study, the DHI, DNR, and COIN values were 0.57, 0.43, and 0.72, respectively, similar to Swetha et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma et al used Paris technique for dose prescription and found that DHI, DNR, and COIN were 0.61, 0.31, and 0.79, respectively [22]. Swetha et al reported DHI, DNR, and COIN as 0.57, 0.43, and 0.73, respectively, in their study using inverse planning technique [23]. In the present study, the DHI, DNR, and COIN values were 0.57, 0.43, and 0.72, respectively, similar to Swetha et al…”
Section: Discussionmentioning
confidence: 99%
“…Swetha et al . reported DHI, DNR, and COIN as 0.57, 0.43, and 0.73, respectively, in their study using inverse planning technique [ 23 ]. In the present study, the DHI, DNR, and COIN values were 0.57, 0.43, and 0.72, respectively, similar to Swetha et al .…”
Section: Discussionmentioning
confidence: 99%
“…ODI 11 is the ratio of the target volume that receives a dose equal to or more than twice the reference dose. [11][12][13][14] is defined as the ratio of high-dose volume relative to the reference volume. DNR is used to evaluate the quality of the plan.…”
Section: Methodsmentioning
confidence: 99%
“…This model can be used for both tumors and normal tissues. Several quality factors were calculated in this study, as used by various reports in the literature (12,13) …”
Section: Methodsmentioning
confidence: 99%